Various therapies in the treatment of patients with medial compartment osteoarthritis of knee joint: A review of literature - Behnam Soleymani; Mostafa Kamali; Ali Tahmasebi; Tahmoureth Tahmasebi (مجله پژوهش در علوم توانبخشی, 2015)
Introduction: knee joint osteoarthritis is one of the most prevalent musculoskeletal problems in adult population, which cause pain and functional limitations. Involvement of medial compartment is almost 10 times more common than lateral compartment, which results in varus deformity among patients with medial compartment osteoarthritis of knee joint. Main objectives in the treatment of knee joint osteoarthritis are reducing pain, improving physical functions and reducing the progress of the disease. Treatments of knee joint osteoarthritis are classified in two categories: operative treatment and conservative treatment. The aim of this study is to investigate the effect of different therapies in the treatment of patients with medial compartment osteoarthritis of knee joint.